Prediction of Metabolite‐to‐Parent Drug Exposure: Derivation and Application of a Mechanistic Static Model - Ernesto Callegari; Manthena V.S. Varma; R. Scott Obach (Wiley, 2020)
In the development of new drugs, the prediction of metabolite‐to‐parent plasma exposure ratio in humans prior to administration in a clinical study has emerged as an important need. In this work, we derived a mechanistic static model based on first principles to estimate metabolite‐to‐parent plasma exposure ratio, considering the contribution of liver and gut metabolism and drug transport. Knowledge (or assumptions) of mechanisms of clearance and organs involved is required. Input parameters needed included intrinsic clearance, fraction of clearance to the metabolite of interest, various binding values, and, in some cases, active transport clearance. The principles are illustrated with four drugs that yield six metabolites, with one in which clearance is dependent on a pathway subject to genetic polymorphism. Overall, the approach yielded metabolite‐to‐parent ratios within about twofold of the actual values and, thus, can be valuable in decision making in the drug development process.